IDENTIFYING AND UNDERSTANDING THE PATTERNS AND PROCESSES OF FOREST COVER CHANGE IN ALBANIAAND KOSOVO - Laze, Kuenda (European Scientific Journal, ESJ, 2014)
Forests are important resources for local livelihoods and the economy. Forests regulate climate by sequestrating and storing carbon and harbor significant biodiversity. Yet, forest cover can be significantly affected by changes in institutional and political framework conditions such as induced by the collapse of socialism in Eastern Europe and the war in Kosovo. This study analyzes the patterns of changes in forest cover for a period from 1988 to 2000 and from 2000 and 2007 for Albania and Kosovo. The methodological approach applied geographically weighted regression using remote sensing forest data. Three models were developed and fitted using these forest data: one based on the environmental factors and two models associated with demographic and policy variables. The decomposition of local variation of the relationships of the forest cover change and variables was undertaken to builtup a hierarchy of determinants. Policy model included protected areas, commune forests, accessible determinants and obtained the lowest Corrected Akaike Information values, and accessible variables were the determinants explaining the patterns of forest cover changes in the study area. It is demonstrated how the results of the descriptive statistics and models can be incorporated to investigate the changes of forested landscape at country-level and villagelevel. Descriptive statistics demonstrated deforestation in protected areas and the modeling in the surroundings of protected areas. These results show clearly forest reforms, institutions and users contribute to the changes of forested landscape, indicating the importance of collaboration between institutions and users to monitoring of all activities in forests.